2017
DOI: 10.1007/s11103-017-0645-1
|View full text |Cite
|
Sign up to set email alerts
|

The maize CorA/MRS2/MGT-type Mg transporter, ZmMGT10, responses to magnesium deficiency and confers low magnesium tolerance in transgenic Arabidopsis

Abstract: ZmMGT10 was specifically expressed in maize roots and induced by a deficiency of magnesium. Overexpression of ZmMGT10 restored growth deficiency of the Salmonella typhimurium MM281 strain and enhanced the tolerance in Arabidopsis to stress induced by low magnesium levels by increasing uptake of Mg via roots. CorA/MRS2/MGT-type Mg transporters play a significant role in maintaining magnesium (Mg) homeostasis in plants. Although the maize CorA/MRS2/MGT family comprises of 12 members, currently no member has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…The double mutant mgt6 mgt7 showed more severe phenotypes compared with single mutants under both low‐ and high‐Mg conditions, indicating that these two MGT‐type transporters play additive roles in controlling plant Mg 2+ homeostasis under a wide range of external Mg concentrations (Yan et al ., 2018). Transgenic A. thaliana plants overexpressing ZmMGT10 exhibited longer root length, higher shoot weight, chlorophyll content and Mg 2+ uptake under low Mg conditions, thus suggesting that ZmMGT10 is essential for plant growth and development (H. Li et al ., 2017).…”
Section: Magnesiummentioning
confidence: 99%
“…The double mutant mgt6 mgt7 showed more severe phenotypes compared with single mutants under both low‐ and high‐Mg conditions, indicating that these two MGT‐type transporters play additive roles in controlling plant Mg 2+ homeostasis under a wide range of external Mg concentrations (Yan et al ., 2018). Transgenic A. thaliana plants overexpressing ZmMGT10 exhibited longer root length, higher shoot weight, chlorophyll content and Mg 2+ uptake under low Mg conditions, thus suggesting that ZmMGT10 is essential for plant growth and development (H. Li et al ., 2017).…”
Section: Magnesiummentioning
confidence: 99%
“…The induction of root Mg 2+ uptake is characterised in Arabidopsis (Ogura et al, 2018) and rice (Tanoi et al, 2014), and Mg 2+ transporter family MITOCHONDRIA RNA SPLICING 2/MAGNESIUM TRANSPORTER (MRS2/MGT; Schock et al, 2000;Li et al, 2001) is indicated to be putatively responsible (Mao et al, 2014;Ogura et al, 2018). However, there is uncertainty regarding the root transcriptional regulation of MRS2/MGT genes with some reports suggesting that Mg deficiency induces root transcript levels of MRS2/MGT (Mao et al, 2014;Li et al, 2017;Liu et al, 2019) and others suggesting no transcriptional induction of MRS2/MGT (Gebert et al, 2009;Hermans et al, 2010a,b;Ogura et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In Oryza sativa , OsMGT1 was found to play an important role in the tolerance to Al toxicity and salt stress [23]. In maize, ZmMGT10 is essential in response to Mg deficiency, and confers low Mg tolerance when the ZmMGT10 gene is overexpressed in Arabidopsis thaliana [24].…”
Section: Introductionmentioning
confidence: 99%